Job Search Behaviors of Vocational and General High School Graduates: A Comparative Research - Hidayat, Rinintha; Lieandy, Johanes Agung; Bimantoro, Danto Adhitya; Prasetyaningtyas, Sekar Wulan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study examines senior high school and vocational high school graduates' job search outcomes in Banten and West Java, Indonesia, high-unemployment regions. It examines how financial hardships, self-efficacy, and social support affect job search behaviors and outcomes. Survey research uses questionnaires to collect data. A cross-sectional time horizon is used to capture job search behavior in a non-contrived setting. Data from 512 female participants was analyzed to determine how variables affected job search outcomes. Data suggests that vocational high school graduates have stronger relationships between self-efficacy, job search behaviors, and outcomes than general high school graduates. It's important to tailor job search support and interventions to different educational backgrounds. This study sheds light on how financial hardship, self-efficacy, and social support affect job search behaviour and outcomes for Indonesian general and vocational high school graduates. For vocational graduates, self-efficacy indirectly affects job search outcomes through job search behaviors more than for general graduates. Vocational graduates are more affected by job search behaviors than general high school graduates. These findings demonstrate the differences in job search dynamics between educational backgrounds and suggest ways to tailor career support interventions to Indonesia's demographic bonus and Golden Indonesia 2045 vision.